Trajectory and Leadership Formation of Mexican Women Scholars: The Morelos Case - Montes-de-Oca-O'Reilly, Alejandra; Yurén Camarena, Teresa (Education Policy Analysis Archives, 2010)
This article is a qualitative analysis of trajectories and leadership formación of twelve scholarly leaders who work at five institutions in the state of Morelos, in Mexico. We analyze three categories of formative experiences: a) formative experiences within the family, b) scholar and professional formative experiences and c) formative experiences aside from the domestic, scholar and professional spheres. Based on our study, we suggest the following factors in the formación of leaders: sociomoral formación, mentoring by support figures and guide figures, search for autonomy, exposure to problematic situations that represent a challenge, setting of long-range goals, generation of dispositions to resist an instrumental logic, exposure to leadership figures, as well as an increase in social and cultural capital. We emphasize the importance of the existential as well as the ethical and political dimensions in leadership formation.